First viral replication of Covid-19 identified in the peritoneal dialysis fluid of a symptomatic patient - Mathilde Nouvier; Elodie Chalençon; Etienne Novel-Catin; Solenne Pelletier; Patrick Hallonet; Caroline Charre; Laetitia Koppe; Denis Fouque (RDPLF, 2020)
The COVID-19 pandemic is characterized by a disease with mainly respiratory tropism and varying severity. Viral excretion of COVID-19 has been described in both urine and stool  with the risk of contamination by stool. No viral replication in the peritoneal dialysis fluid has been reported to date. We report an observation demonstrating the presence of the virus in the peritoneal dialysis drainage fluid of a COVID-19 patient. This underlines the importance in COVID-19 patients of considering dialysis fluid as a possible source of contamination.